2009
DOI: 10.1038/modpathol.2009.115
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase expression by Barrett's epithelium and during esophageal carcinoma progression

Abstract: Enzymatic activity responsible for the cleavage of heparan sulfate, commonly known as heparanase, is abundant in tumor-derived cells. Heparanase cleaves heparan sulfate side chains, presumably at sites of low sulfation, thus facilitating structural alterations of the extracellular matrix and basement membrane underlying epithelial and endothelial cells. Traditionally, heparanase activity was correlated with the metastatic potential of tumor-derived cells, attributed to enhanced cell dissemination as a conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
0
21
0
Order By: Relevance
“…In several examples (i.e., colon and esophagus) (36, 37), heparanase expression is induced already at the very early stages of tumor initiation. Results of the current study suggest that elevated levels of heparanase early on have a prominent impact on tumor expansion and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In several examples (i.e., colon and esophagus) (36, 37), heparanase expression is induced already at the very early stages of tumor initiation. Results of the current study suggest that elevated levels of heparanase early on have a prominent impact on tumor expansion and aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of Barrett's oesophagus to adenocarcinoma (Picardo et al, 2012); chronic gastritis to intestinal-type gastric carcinoma, chronic hepatitis C to hepatocellular carcinoma (Chiba et al, 2012); pancreatitis to pancreatic adenocarcinoma (Lowenfels et al, 1993) and colitis to colorectal cancer (Gupta et al, 2007) are well-known examples of inflammation-driven tumorigenesis. Remarkably, induction of heparanase prior to the appearance of malignancy was reported in essentially all of the above-mentioned inflammatory conditions, i.e., Barrett's oesophagus (Brun et al, 2009; Sonoda et al, 2010), hepatitis C infection (El-Assal et al, 2001), chronic pancreatitis (Koliopanos et al, 2001), Crohn disease and ulcerative colitis (Lerner et al, 2011; Waterman et al, 2007). Given the causal role the enzyme plays in tumor progression in tissues in which cancer-related inflammation typically occurs [i.e., gastrointestinal tract, pancreas, liver (Brun et al, 2009; El-Assal et al, 2001; Hoffmann et al, 2008; Koliopanos et al, 2001; Naomoto et al, 2005; Nobuhisa et al, 2005; Sonoda et al, 2010; Xiong et al, 2012; Zhang et al, 2007)], it is conceivable that inflammation-induced heparanase may be involved in coupling inflammation and cancer.…”
Section: Heparanase In Inflammationmentioning
confidence: 99%
“…Remarkably, induction of heparanase prior to the appearance of malignancy was reported in essentially all of the above-mentioned inflammatory conditions, i.e., Barrett's oesophagus (Brun et al, 2009; Sonoda et al, 2010), hepatitis C infection (El-Assal et al, 2001), chronic pancreatitis (Koliopanos et al, 2001), Crohn disease and ulcerative colitis (Lerner et al, 2011; Waterman et al, 2007). Given the causal role the enzyme plays in tumor progression in tissues in which cancer-related inflammation typically occurs [i.e., gastrointestinal tract, pancreas, liver (Brun et al, 2009; El-Assal et al, 2001; Hoffmann et al, 2008; Koliopanos et al, 2001; Naomoto et al, 2005; Nobuhisa et al, 2005; Sonoda et al, 2010; Xiong et al, 2012; Zhang et al, 2007)], it is conceivable that inflammation-induced heparanase may be involved in coupling inflammation and cancer. The findings obtained in a study utilizing mouse model of colitis-associated colon carcinoma support this notion (Lerner et al, 2011).…”
Section: Heparanase In Inflammationmentioning
confidence: 99%
“…Therefore, the observed increase in nMuMG cell proliferation in cells incubated with cM may at least in part be due to the stimulation of this enzyme's activity. an increase in heparanase activity has previously been described in relation to an increase in the metastatic activity of tumor cells (8); however, our findings indicate that heparanase may also be involved in the proliferation of normal breast epithelial cells (22). in terms of MMP-9 activity, basal expression was observed in the nMuMG cells, and was not modified following incubation with any of the three types of cM.…”
Section: Discussionmentioning
confidence: 38%
“…in this study, we demonstrated that the state of adipocyte differentiation influences normal and tumoral breast epithelial cell proliferation and migration. Heparanase and MMP-9 are potentially involved in this regulation (22). The proliferation of NMuMG cells was significantly increased in cells incubated with the three types of conditioned media, as well as in cells grown on the prea, pda and Ma 3T3-l1 stromal support cells.…”
Section: Discussionmentioning
confidence: 84%